Intubation of a Patient with a Large Goiter: The Advantageous Role of Videolaryngoscopy. (5th December 2019) - Heinz, Eric; Quan, Theodore; Nguyen, Hieu; Pla, Raymond
Abstract : Fiberoptic bronchoscopy has long been considered the gold standard for patients who present with a difficult airway. In the case presented, a patient has a large palpable goiter and requires intubation. After the unsuccessful attempt to intubate with the use of fiberoptic bronchoscopy, the decision to switch to videolaryngoscopy afforded a positive result. We present this case to suggest that the utilization of videolaryngoscopy may be an alternative option for intubation when other methods have failed. It is imperative for anesthesiologists to understand the benefits that this modality may provide.